The Role of Green Human Resource Practices in Fostering Green Corporate Social Responsibility - Hameed, Rizwana; Mahmood, Asif; Shoaib, Muhammad (Frontiers in Psychology, 2022)
This study develops a conceptual framework and investigates green human resource practices (GHRM)—green recruitment and selection, green training and development, and green reward and compensation? effects on pro-environmental psychological climate and pro-environmental behavior, which cause green corporate social responsibility (GCSR). We employ information technology (IT) capabilities as a moderator between the GHRM and pro-environmental behavior. It applies a convenience sampling technique and survey questionnaire to collect data from 388 employees at CPEC projects. Results demonstrate that GHRM positively influences pro-environmental psychological climate and pro-environmental behavior that significantly develops GCSR. IT capabilities significantly moderate the relationships between GHRM and pro-environmental behavior. The study findings add to the body of green HRM practices, strategic management, and information processing and policy makers better postulate, align, and exercise their green HRM practices for its synergetic effects for green CSR and sustainability. We also acknowledge some limitations and provide future directions.